2005
DOI: 10.1192/apt.11.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Learning disability in the accident and emergency department

Abstract: Generally, people with learning disabilities now live in community settings and use generic health services. Those who develop behavioural or psychiatric disturbances may be taken to a hospital accident and emergency (A&E) department. An A&E visit can be the starting point of a comprehensive assessment of these disturbances. This article provides a framework for the initial assessment, management and disposition of patients with learning disabilities and behavioural disturbance presenting to an A&E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 2 publications
0
50
1
1
Order By: Relevance
“…They visit hospital EDs frequently, even though the ED is not an ideal environment for them. 7,25,26 As severity of psychiatric comorbidity increases, ED use cannot simply be attributed to poor access to either primary or psychiatric care. Rather, increased ED use among people with DD and concurrent psychiatric illness occurs despite reasonable access to primary care and specialty services, compared with access by people without DD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They visit hospital EDs frequently, even though the ED is not an ideal environment for them. 7,25,26 As severity of psychiatric comorbidity increases, ED use cannot simply be attributed to poor access to either primary or psychiatric care. Rather, increased ED use among people with DD and concurrent psychiatric illness occurs despite reasonable access to primary care and specialty services, compared with access by people without DD.…”
Section: Discussionmentioning
confidence: 99%
“…3 These people access mental health services younger and more frequently than people with psychiatric disorders but no DD 4,5 and are frequent users of EDs. 6 It has been suggested that ED visits by people with psychiatric disorders with DD occur, in part, because other resources are inadequate 7,8 and thus serve as a barometer of the adequacy of primary and specialty outpatient care. A recent study found that lack of primary care predicted ED use in a sample of adults with DD experiencing psychiatric crisis, when adjusting for age, sex, residential setting, and disability severity.…”
Section: Abbreviationsmentioning
confidence: 99%
“…It has been well established that individuals with ID are at greater risk of developing physical and mental health problems or serious challenging behaviors compared with the general population (Cooper, Smiley, Morrison, Williamson, & Allan, 2007;Emerson & Hatton, 2007;van Shrojenstein Lantman-De Valk, Metsemakers, Haveman, & Crebolder, 2000). These health needs are often unrecognized and unmet (U.S. Department of Health and Social Services, 2002), which in turn can precipitate behavioral crisis (Bradley & Lofchy, 2005;P. W. Davidson et al, 1994;Lunsky, Gracey, & Gelfand, 2008).…”
mentioning
confidence: 99%
“…The fact that these items appear to form a consistent hierarchy across individuals suggests that the additional difficulties experienced by people at risk of having an intellectual disability can be predicted from other reported difficulties. This should facilitate the optimal allocation of support and is likely to be helpful to professionals who do not have specialized knowledge of intellectual disability and to whom the individual is unknown but who have some indication of a person's support needs within contexts such as emergency admission to hospital (Bradley & Lofchy, 2005) Often, language difficulties and socially desirable responding can make obtaining accurate information about a person's functioning through self-report a challenge. Where full information on functioning is not available, scales with Mokken properties can be used to estimate that missing information on the basis of the information that is available.…”
Section: Discussionmentioning
confidence: 99%